2012
DOI: 10.7498/aps.61.124211
|View full text |Cite
|
Sign up to set email alerts
|

Coherence properties of the supercontinuum generated in anomalous dispersion region of photonic crystal fibers

Abstract: We numerically calculated the coherence properties of the supercontinuum based on the definition of complex degree of mutual coherence, and obtained the spectral broadening of the pump pulse and the coherence properties of the generated supercontinuum under different pump powers. The results showed that the dominant underlying mechanisms of the spectral broadening are soliton self-frequency shift and dispersive wave generation when the pump wavelength located in the anomalous dispersion region of photonic crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Laser transmission in the atmosphere is mainly affected by atmospheric attenuation, turbulence and background radiation [1][2][3] , where atmospheric attenuation causes extinction effects and turbulence causes random fluctuations in laser phase. In recent years, researchers have found that partially coherent lasers can reduce the effect of turbulence on transmission 4,5 , while the unique characteristics of supercontinuum with good spatial coherence and low temporal coherence are well suited for atmospheric transmission studies 6 . The supercontinuum laser also has the characteristics of wide spectrum, high brightness, good directionality [7][8][9] , which possess prevailing advantages in atmospheric transmission research [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Laser transmission in the atmosphere is mainly affected by atmospheric attenuation, turbulence and background radiation [1][2][3] , where atmospheric attenuation causes extinction effects and turbulence causes random fluctuations in laser phase. In recent years, researchers have found that partially coherent lasers can reduce the effect of turbulence on transmission 4,5 , while the unique characteristics of supercontinuum with good spatial coherence and low temporal coherence are well suited for atmospheric transmission studies 6 . The supercontinuum laser also has the characteristics of wide spectrum, high brightness, good directionality [7][8][9] , which possess prevailing advantages in atmospheric transmission research [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of high index PCF for SC generation is cuttingedge research in the field of photonics. [6,7] Many unusual properties can be achieved, including the range of transmission extending to mid-infrared, [8] the zero dispersion wavelength (ZDW) up to 2.0 µm, [9] and the ultraflat SC generation. [10] SC generation provides a broadband optical source for the optical frequency metrology, [11] frequency comb generation, [12] and optical coherence tomography.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Since the magnitude of the soliton self-frequency shift inversely increases with the increasing pulse duration, the soliton self-frequency shift of the solitons created after fission leads to a red spectral broadening in the PCF with anomalous group velocity dispersion. [10][11][12][13][14] At the same time, the dispersive wave generation extends the spectrum into the visible and the ultraviolet spectral ranges where the group velocity dispersion is normal.…”
Section: Introductionmentioning
confidence: 99%